Language Awareness in an Internet Chat Room - Szymański, Leszek (Respectus Philologicus, 2013)
When communicating on the Internet, the participants, so to say, mingle two traditional modes of communication: writing and speech. The phenomenon appears to be most noticeable in chat room interactions. This suggestion is based on the fact that users try to behave as though they are engaged in a spoken act of communication, though the actual medium of communication employs written language forms. Therefore, Internet users need to know what conventions to employ and how to perform such actions in order to express the desired meanings, all with the aim of driving the interaction as close as possible to speech. Such implementations of certain language-related customs require a specific kind of language awareness from the users. This concept, plus the applied conventions, constitute the essence of this article. The discussion begins with an introduction to the research problem, in this case the intentional utilization by Internet chat participants of the graphic mode of communication in order to express their desired meanings. Second, the reader becomes acquainted with the terminology used in the paper, which includes: language awareness, (Internet) chat, and (language) corpus. Moreover, the source of the studied language material—a corpus of Internet chats—is presented. The said description additionally includes the informants’ characteristics, as well as the topicality of their conversations. The further sections of the paper discus the application of selected non-normative spelling conventions and word-formation processes, with the support of examples taken from the corpus. Based on the discussion, an attempt is made to indicate which features comprise certain values to the participants of Internet chats.